Structuring Information Work: Ferranti and Martins Bank, 1952-1968. - Martin, Ian (Information & Culture, 2012)
The article explores the history of computers in banking in Great Britain by focusing particularly on the Ferranti and Martins Bank between 1952 and 1968. It describes how the adaptation of computer technologies by British retail banks forced the centralization of banking information from various branch banks to separate regional banking centers. The theory of structuration forwarded by sociologist Anthony Giddens is considered.